Sleep duration and the risk of breast cancer: the Ohsaki Cohort Study - Kakizaki, M (Nature Publishing Group, 2008)
In a prospective study of 23 995 Japanese women, short sleep duration was associated with higher risk of breast cancer (143 cases), compared with women who slept 7 h per day, the multivariate hazard ratio of those who slept ⩽6 h per day was 1.62 (95% confidence interval: 1.05–2.50; P for trend=0.03).